Acceptability of delivering an adapted Buurtzorg model in the Scottish care context. (February 2020) - Leask, C.F.; Bell, J.; Murray, F.
Abstract: Objectives: Given increasing epidemiological and financial pressures on services, there is a need to test new models of integrated health and social care. Crucial to this testing is determining acceptability, particularly to those delivering services. The Dutch 'Buurtzorg' model, characterised by self-managing nursing teams, has shown promise, but its principles are yet to be adapted and tested in Scotland. The study aim was to understand the experiences of working in a self-managing, integrated, health and social care team. Study design: This is a case study within a primary care setting. Methods: The Integrated Neighbourhood Care Aberdeen (INCA) project comprised two self-managing teams of support workers and nurses working at different sites in Aberdeen. Acceptability was explored through semistructured interviews with staff. Data were recorded and analysed thematically. Results: Staff reported high-quality patient care, which they attributed to autonomy over the frequency and duration of visits. Tensions between team members and between teams and management were apparent partly due to the predominantly social care caseload, confounding guidance on how to implement self-management and communication challenges. The team colocated within a General Practice reported positive relationships with other professionals. Conclusions: Self-management requires a clear framework in which to function. Allowing staff autonomy to vary care provision according to need may improve patient outcomes. Highlights: Co-location may improve collaboration and job satisfaction of health and social care professionals. Self-managing teams require a clear framework to effectively operate. Staff's autonomy to fluctuate frequency and duration of patient support may improve outcomes.